2008
DOI: 10.2117/psysoc.2008.28
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Individual Differences and Irrelevant Speech on WCST and Stroop Test

Abstract: This study examines the irrelevant speech effect (ISE) and the effects of individual differences (introversion/extroversion and field dependence/independence: FDI) on the Wisconsin Card Sorting Test (WCST) and the Stroop Test. In Experiment 1, irrelevant speech and silence groups performed the WCST. Unlike the ISE, FDI affected four WCST indexes (CA, TE, PE [Milner], and PE [Nelson]) but did not affect the WCST DMS index, which shows the difficulty of maintaining concepts. However, the ISE was observed with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…This channel measured activity in the right dorsolateral prefrontal cortex, which is related to working memory and plays a monitoring role in solving problems [ 27 , 28 ]. Stuss et al reported that patients with damage to the right dorsolateral prefrontal cortex showed impaired performance on the Wisconsin Card Sorting Test [ 29 ], which is designed to evaluate concept formation and conversion ability [ 30 ]. Hyperactivation of this area contributes to the switching of consciousness and the formation of intention.…”
Section: Discussionmentioning
confidence: 99%
“…This channel measured activity in the right dorsolateral prefrontal cortex, which is related to working memory and plays a monitoring role in solving problems [ 27 , 28 ]. Stuss et al reported that patients with damage to the right dorsolateral prefrontal cortex showed impaired performance on the Wisconsin Card Sorting Test [ 29 ], which is designed to evaluate concept formation and conversion ability [ 30 ]. Hyperactivation of this area contributes to the switching of consciousness and the formation of intention.…”
Section: Discussionmentioning
confidence: 99%